2021
DOI: 10.1155/2021/6643382
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Oxidative Stress and Ferroptosis/Oxytosis in Ischemic Stroke: Possible Targets and Molecular Mechanisms

Abstract: Oxidative stress is a key cause of ischemic stroke and an initiator of neuronal dysfunction and death, mainly through the overproduction of peroxides and the depletion of antioxidants. Ferroptosis/oxytosis is a unique, oxidative stress-induced cell death pathway characterized by lipid peroxidation and glutathione depletion. Both oxidative stress and ferroptosis/oxytosis have common molecular pathways. This review summarizes the possible targets and the mechanisms underlying the crosstalk between oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 147 publications
(247 reference statements)
6
59
0
Order By: Relevance
“…During ischemic stroke, as the artery that supplies blood to the brain is blocked, the brain cells do not receive blood supply properly and so they are glucose and oxygen-deprived. This results in ATP level depletion and rises the intracellular calcium levels [28], which causes mitochondrial injury, free radical generation, and damages the nucleus and, cell membrane, and eventually leading to cell death [28,29]. As expected, our data showed that high glucose and H/R injury increased the cytotoxicity, oxidative stress and eventually reduced the viability of astrocytes, indicating the success of the injury model.…”
Section: Discussionsupporting
confidence: 71%
“…During ischemic stroke, as the artery that supplies blood to the brain is blocked, the brain cells do not receive blood supply properly and so they are glucose and oxygen-deprived. This results in ATP level depletion and rises the intracellular calcium levels [28], which causes mitochondrial injury, free radical generation, and damages the nucleus and, cell membrane, and eventually leading to cell death [28,29]. As expected, our data showed that high glucose and H/R injury increased the cytotoxicity, oxidative stress and eventually reduced the viability of astrocytes, indicating the success of the injury model.…”
Section: Discussionsupporting
confidence: 71%
“… 212 From another perspective, ferroptosis is also closely associated with oxidative stress, in which signaling pathways such as calcium-related signals, ATF4 and Keap1-Nrf2 signaling pathways play a role. 213 Despite being less frequently discussed, ferroptosis may also be greatly involved in the pathogenesis of ischemic stroke,with a variety of signaling pathways potentially participating in.…”
Section: Pathophysiology and Signaling Pathways Involved In Ischemic ...mentioning
confidence: 99%
“…Oxidative stress and lipid peroxidation are key events of ferroptosis [ 26 , 27 ]. LncRNA MALAT1 promotes oxidative stress and ROS production in many diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%